Does Profitability Affected On Intellectual Capital? - Hamdani, Deni (JAAF (Journal of Applied Accounting and Finance), 2025)
The purpose of this research is to examine how Return on Asset is impacted by Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), and Structural Capital Value Added (STVA).   Basic Materials firms that were listed on the Indonesia Stock Exchange between 2016 and 2023 were the subject of this study.   Utilizing data gathering methods gleaned from documentation and literature research, this study is categorized as quantitative research with a descriptive and verificative approach.   Purposive sampling was the method employed in the sampling procedure.   Multiple linear regression analysis is used for data analysis, and IBM SPSS 26.0 is used for data processing. The partial t-test research results show that Value Added Capital Employed significantly affects Return On Asset, but Value Added Human Capital and Structural Capital Value Added have little influence. Value Added Capital Employed, Value Added Human Capital, and Structural Capital Value Added all significantly and favorably affect Return on Asset, according to the research findings in the simultaneous F-test